Consumer perceived risk, risk reduction strategies and transaction intentions in online marketplaces - Nissilä, Maija (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Even though online commerce has garnered vast academic interest during the recent years, theoretical grounds for consumer behavior online still remains ambiguous. Despite the globally rapid growth of online commerce, only a fraction of Internet browsers end up purchasing goods online. This is argued to be caused by the intangible and distant nature of the Internet, causing overwhelming perceived risks for consumers and negatively affecting transaction intentions. To combat perceived risks, consumers may actively or passively seek to relieve those risks to tolerable level. These risk reduction strategies refer to both institutional mechanisms as well as consumer risk reduction strategies. The objective of this thesis is to provide further understanding upon the relationships between consumer perceived risk, risk reduction strategies and transaction intentions in online marketplaces. To serve the objectives of the present thesis, a quantitative approach was chosen as the method for conducting empirical research. The data was collected with an online survey through discussion board, using a random sample approach. The proposed research model was examined with a set of hierarchical regression analyses. Results revealed several direct relationships as well as moderating interaction effects. The key finding of this thesis is that institutional risk reduction mechanisms significantly contribute to consumer perceived risks. These mechanisms have the potential to reduce perceived risks, and therefore may stimulate transaction intentions. Additionally, it was observed that risk reduction strategies moderate the relationship between intermediary provided risk relievers, consumer perceived risks and transaction intentions. Retailer related risk reduction strategies were also shown to enforce the effectiveness of payment methods; however feedback and monitoring mechanism was shown to have a diminishing effect of perceived risk only when consumers did not rely on product related risk reduction strategies. The present thesis also illustrates the importance of effective information search, as those consumers are more willing to transact as the perceived risks become less significant. For managerial purposes, the importance of well-functioning institutional mechanisms cannot be emphasized enough.